Failure of Primary Total Hip Arthroplasty Secondary to New Onset of Paget Disease: A Case Report. Issue 1 (January 2015) - Amundsen, Spencer; Koenig, Karl; Goodwin, Douglas; Memoli, Vincent
Abstract : Case: Paget disease of bone occurs in 3% to 4% of the population over fifty years of age, more often in men than in women. There is no known genetic basis for the disease, which is often diagnosed via incidental radiographic findings. We present a seventy-seven-year-old man with new-onset Paget disease after total hip arthroplasty, leading to loosening of the femoral stem and necessitating revision. Conclusion: This case emphasizes the need for thoughtful evaluation of patients with failed arthroplasty and proposes steps for an appropriate workup prior to revision surgery.